2015
DOI: 10.18632/oncotarget.4128
|View full text |Cite
|
Sign up to set email alerts
|

Ataxin-3 like (ATXN3L), a member of the Josephin family of deubiquitinating enzymes, promotes breast cancer proliferation by deubiquitinating Krüppel-like factor 5 (KLF5)

Abstract: The Krüppel-like factor 5 (KLF5) has been suggested to promote breast cell proliferation, survival and tumorigenesis. KLF5 protein degradation is increased by several E3 ubiquitin ligases, including WWP1 and SCFFbw7, through the ubiquitin-proteasome pathway. However, the deubiquitinase (DUB) of KLF5 has not been demonstrated. In this study, we identified ATXN3L as a KLF5 DUB by genome-wide siRNA screening. ATXN3L directly binds to KLF5, decreasing its ubiquitination and thus degradation. Functionally, knockdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…Given the important role of p53 in neurodegenerative diseases and cancer, it is thus a likely possible candidate. Recent studies have reported that ATX-3 and ATX-3 like are involved in gastric cancer [63] and breast cancer [64], supporting the association of the Josephin family of DUBs with cancer. Importantly, aberrant activation of the p53 pathway has previously been reported in both MJD patient brain tissues and transgenic animal disease models [6569], and elevated p53 level was observed in MJD transgenic mice [65].…”
Section: Discussionmentioning
confidence: 89%
“…Given the important role of p53 in neurodegenerative diseases and cancer, it is thus a likely possible candidate. Recent studies have reported that ATX-3 and ATX-3 like are involved in gastric cancer [63] and breast cancer [64], supporting the association of the Josephin family of DUBs with cancer. Importantly, aberrant activation of the p53 pathway has previously been reported in both MJD patient brain tissues and transgenic animal disease models [6569], and elevated p53 level was observed in MJD transgenic mice [65].…”
Section: Discussionmentioning
confidence: 89%
“…Scale bar: 0.2 amino acid changes per site. (Frontelo et al, 2007;Nuez et al, 1995;Ouyang et al, 1998;Perkins et al, 1995;Siatecka et al, 2007;Zhang et al, 2001b) (Anderson et al, 1995;Basu et al, 2005;Carlson et al, 2006;Kuo et al, 1997a;Kuo et al, 1997b;Lee et al, 2006;Nakagawa et al, 2008;Wang et al, 2013;Wani et al, 1999a,b;Wu et al, 2005;Xie et al, 2011;Zhang et al, 2004 (Chaib et al, 2001;Chen et al, 2002;Chen et al, 2005a;Conkright et al, 1999;Du et al, 2007;Ge et al, 2015;He et al, 2009;Liu et al, 2010;McConnell et al, 2009;McConnell et al, 2007;Nakagawa et al, 2008;Nandan et al, 2010;Nandan et al, 2008;Oishi et al, 2008;Oishi et al, 2005;Qin et al, 2015;Shindo et al, 2002;Shinoda et al, 2008;Takeda et al, 2010;Tong et al, 2006;Wan et al, 2008;...…”
Section: Other Endoderm-derived Organsmentioning
confidence: 99%
“…KLF5 (Krüppel-like factor 5) is a zinc finger transcription factor that is highly expressed in basal-like breast cancer and promotes cell proliferation, survival, migration, and tumorigenesis [61]. A recent study identified ATXN3L, a member of the MJD family, as a KLF5 DUB by siRNA screening [61].…”
Section: Breast Cancer-promoting Dubsmentioning
confidence: 99%
“…A recent study identified ATXN3L, a member of the MJD family, as a KLF5 DUB by siRNA screening [61]. ATXN3L directly binds, deubiquitinates, and stabilizes KLF5.…”
Section: Breast Cancer-promoting Dubsmentioning
confidence: 99%
See 1 more Smart Citation